Locally Welded Silver Nano‐Network Transparent Electrodes with High Operational Stability by a Simple Alcohol‐Based Chemical Approach. (27th May 2015) - Lu, Haifei; Zhang, Di; Cheng, Jiaqi; Liu, Jian; Mao, Jian; Choy, Wallace C. H.
Abstract : As an indispensable aspect of emerging flexible optoelectronics, flexible transparent electrodes, especially those comprised of metal nanowires, have attracted great attentions recently. Welding the nanowire junctions is an effective strategy for reducing the sheet resistance and improving the operational stability of flexible nanowire electrode in practical applications. Herein, a simple alcohol‐based solution approach is proposed to weld crossed silver nanowires by chemically growing silver "solder" at the junctions of the nanowires, forming transparent silver nano‐network electrodes with improved electrical conductivity and operational stability. Remarkably, silver nano‐networks can be rapidly formed by this simple approach under ambient condition and room temperature, requiring no assistance from heat, light, electrical current, or mechanical pressure. Furthermore, our results show that the nano‐network electrode formed from large diameter nanowires offers a better operational stability, whose trend is opposite to that of the untreated electrodes. To demonstrate the potential application of the highly stable silver nano‐network from large diameter nanowires, organic solar cells fabricated on the nano‐network electrode incorporated with silicon dioxide nanoparticles achieve comparable performance to the ITO control device. Consequently, strategy demonstrated in this work can contribute to low‐cost and highly stable transparent electrodes in emerging flexible optoelectronics. Abstract : A simple alcohol‐based solution approach is proposed to weld crossed silver nanowires through a locally chemical welding pathway without any assistance of heat, light, electrical current, or mechanical pressure. In addition, silicon dioxide nanoparticles are used for filling the voids among the nano‐networks to depress electrical shorting and enable their application in organic solar cells.